2008
DOI: 10.1179/136217108x363900
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of joint performance in spot friction welding of 6111-T4 aluminium alloy

Abstract: The effect of process parameters (cycle time, tool speed and axial force) on the specimen temperature measured 2 mm away from the weld in spot friction welding (SFW) of Al 6111-T4 is investigated. The temperatures were correlated to the lap shear load. Results revealed that, to achieve a good joint strength with the maximum lap shear load .2?5 kN, temperatures should be greater than a threshold value, which is 350uC at a location close to the SFW joint in this study. By studying the specimen macrographs, two i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…In particular, the mechanical properties of the joints resulted to be strictly related to the rotational speed. This is in agreement with some studies reported in literature [6,13]. Moreover, the increase of feed rate resulted in a general reduction of mechanical properties while a general increase of the shear resistance was observed for increasing values of the plunging depth.…”
Section: Mechanical Characterizationsupporting
confidence: 95%
See 1 more Smart Citation
“…In particular, the mechanical properties of the joints resulted to be strictly related to the rotational speed. This is in agreement with some studies reported in literature [6,13]. Moreover, the increase of feed rate resulted in a general reduction of mechanical properties while a general increase of the shear resistance was observed for increasing values of the plunging depth.…”
Section: Mechanical Characterizationsupporting
confidence: 95%
“…In some researches it was observed that the lap shear load first increases, and then decreases for increasing values of the tool rotation speed [13]. Other Authors observed that higher weld strength can be related to a wider stir zone size, obtained by limiting the tool rotation speed [14,15].…”
Section: Introductionmentioning
confidence: 94%
“…The flow of lower sheet material displaced upwards changes the inclination of the hook region from downwards in lower sheet material to upwards in the upper sheet material during the dwell period in spot welding. Lathabai et al (2006), Wang and Lee (2007) and Arul et al (2008) previously observed saw-toothed hook profiles in Al-6065-T5, Al-6061-T6 and Al-6111-T4 spot welds. Lathabai et al (2006) suggested that the original interface between upper and lower sheets was severely deformed creating a wavy line, while Arul et al (2008) associated saw-toothed hook profiles with asymmetrical welding nugget geometry and inhomogeneous TMAZ material properties.…”
Section: Discussionmentioning
confidence: 88%
“…Considering the spot welding parameters, it should be noted that some authors stress tool rotational speed as the determining factor of the strength of the joint [2], stating that for select material there is an optimal range of tool rotational speed that results in high strength joints. The research of other authors focused on tool plunge rates, the pin rotational speed ration as the significant determining factors of spot weld quality [18].…”
Section: Introductionmentioning
confidence: 99%